Metodyczne i społeczne aspekty nauczania zdalnego - Piecuch, Aleksander (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
W artykule podjęto próbę analizy wpływu nauczania zdalnego na młodzież uczącą się i studiującą. W obszarze zainteresowań znalazły się komunikacja uczeń/student − nauczyciel/nauczyciel akademicki, kwestie związane z metodyką i organizacją nauczania, technicznymi aspektami kształcenia online oraz psychologicznymi następstwami wprowadzonych obostrzeń sanitarnych.

The article attempts to analyze the impact of distance learning to young people who learning and studying. The area of interest embrace a communication between student and teacher, issues related to the methodology and organization of teaching, technical aspects of online education and psychological consequences of the introduced sanitary restrictions.
Methodical and social aspects of distance learning
Keywords: komunikacja; konstruktywizm; nauczanie zdalne; media cyfrowe; kompe-tencje multimedialne; człowiek; communication; constructivism; distance learning; digital media; multimedia competences; human